2022
DOI: 10.1159/000527677
|View full text |Cite
|
Sign up to set email alerts
|

High-Frequency Deep Sclerotomy as Adjunctive Therapy in Open-Angle Glaucoma Patients

Abstract: Introduction: Glaucoma is a chronic, progressive disease of the optic nerve that can cause vision loss and blindness. High-frequency deep sclerotomy (HFDS) is a novel ab interno procedure used to lower intraocular pressure (IOP). This study aims at examining hypotensive effects of HFDS in patients with medically uncontrolled primary open-angle glaucoma (POAG). Methods: 23 patients (23 eyes) participated in this study. They were all affected by primary open-angle glaucoma and used maximum prescribed medical th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Initial studies investigating the use of HFDS in glaucoma management have shown encouraging results, with significant reductions in IOP and a favorable safety profile [ 32 , 33 , 35 ]. In addition, HDFS can be combined with cataract surgery while avoiding the risk of implant-related complications and has a relatively short learning curve for surgeons already experienced in glaucoma surgery.…”
Section: Devices Procedures and Surgical Techniquesmentioning
confidence: 99%
“…Initial studies investigating the use of HFDS in glaucoma management have shown encouraging results, with significant reductions in IOP and a favorable safety profile [ 32 , 33 , 35 ]. In addition, HDFS can be combined with cataract surgery while avoiding the risk of implant-related complications and has a relatively short learning curve for surgeons already experienced in glaucoma surgery.…”
Section: Devices Procedures and Surgical Techniquesmentioning
confidence: 99%